2018
DOI: 10.1038/s41416-018-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glutaminolysis in chondrosarcoma in context of the IDH1/2 mutation

Abstract: Targeting glutaminolysis with CB-839, metformin, phenformin or chloroquine is a potential therapeutic strategy for a subset of high-grade chondrosarcomas, irrespective of the presence or absence of an IDH1/2 mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
5
39
0
1
Order By: Relevance
“…Likewise, the synthetic lethal interaction between temozolomide and IDH mutations described in gliomas was not observed in our study [35,36]. Our research group published that the reported synthetic lethal interaction between IDH mutations and Bcl-2, NAMPT, and glutaminase inhibition was absent in chondrosarcoma [11,[37][38][39]. Together, these findings indicate that therapeutic strategies in AML and glioma based on IDH mutation status cannot be directly translated to chondrosarcoma.…”
Section: Discussionsupporting
confidence: 42%
“…Likewise, the synthetic lethal interaction between temozolomide and IDH mutations described in gliomas was not observed in our study [35,36]. Our research group published that the reported synthetic lethal interaction between IDH mutations and Bcl-2, NAMPT, and glutaminase inhibition was absent in chondrosarcoma [11,[37][38][39]. Together, these findings indicate that therapeutic strategies in AML and glioma based on IDH mutation status cannot be directly translated to chondrosarcoma.…”
Section: Discussionsupporting
confidence: 42%
“…CB-839 (also known as telaglenastat) is a potent and noncompetitive allosteric GLS1 inhibitor. It exhibits significant anti-proliferative activity in several types of cancer cell lines and xenografts such as triple-negative breast cancer ( Gross et al, 2014 ), lung adenocarcinoma ( Galan-Cobo et al, 2019 ), chondrosarcoma ( Peterse et al, 2018 ), and lymphoma cancer ( Xiang et al, 2015 ). CB-839 is used increasingly in combination to treat cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of 200 mg/kg of CB-839 significantly suppressed the volume of MPNST xenografts [52]. In chondrosarcoma cell lines, CB-839 activity correlated with the status of isocitrate dehydrogenase 1/2 (IDH1/2), as the cells carrying IDH1/2 mutation were more susceptible to this compound than the wild type cells [53]. In a very recent study, CB-839 administered twice daily at dose 200 mg/kg significantly reduced undifferentiated pleomorphic sarcoma (UPS) tumor growth and weight but did not alter animal weights [54].…”
Section: Inhibitors Of Glutaminase (Ga)mentioning
confidence: 99%